Ο Αίσωπος στην οθωμανική γραμματεία του 19ου αι. - Balta, Evangelia (The Gleaner, 2024)
Aesop in the Ottoman Literature of the 19th century The study based on the Karamanlidika version of Aesop’s fables printed by Evangelinos Misailidis in 1854 offers a review of the Ottoman perception of Aesop in the 19th century. The Turkish versions of the fables released in various alphabets (Cyrillic, Arabic), and the Vita of Aesop, are presented and explored. The study also discusses the Turkish manuscript written in Greek characters, located by Ernst Otto Blau in Mariupol, today in southern Ukraine. His discovery proves that Aesop appeared in the handwritten form at least as far back as the 18th century and also indicates that Aesop was introduced to the Ottoman literature by the Turkish-speaking Rums. Unfortunately, the manuscript has not survived, but Blau added excerpts from the life of Aesop and two of his fables in his study published in 1874.